SAKLAR OTOMATIS BERBASIS LIGHT DEPENDENT RESISTOR (LDR) PADA MIKROKONTROLER ARDUINO UNO - Angga Khalifah Tsauqi; Murtezha Hadijaya; Ivander Manuel; Venas Miftah Hasan; Annisa Tsalsabila; Fadhilah Chandra; Titin Yuliana; Putri Tarigan; Irzaman Irzaman (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Has succeeded in making switch automatic based light dependent resistor ( LDR)in mikrokontroler arduino uno .Switch this tested in two conditions yatu in laboraatrium and in roomy .On condition laboratory , voltage enter of 5.00 volts managed to turn switch , where switch burns in the state of life ( ON ) producing a voltage of 3.74 volts and obstacles of 230 -260 ohm , while switch die ( OFF ) producing a voltage of 4.78 volts and obstacles switch of 44 - 45 ohm , with strong lighting in laboratoium at 15 lux is the verge of a function of switch in the laboratory .On condition in roomy , strong lighting the function switch of 70 lux with obstacles switch equal to 100 ohm .The difference the function obstacles switch this caused by the strong illumination that produced by a lamp in the laboratory compared with strong illumination that produced by the eye day . Kata kunci: saklar otomatis, LDR, mikrokontroler,kuat penerangan, lux.